STUDYING HISTORY IN AN ISLAMIC CONTEXT AND ITS EFFECTS ON STUDENT AWARENESS: A CASE STUDY OF MUSLIM STUDENTS AT SAUDI UNIVERSITIES - Alghamdi, Hasnah; Achour, Meguellati (Journal of Al-Tamaddun, 2020)
This study measures the effects of studying history on cultural awareness of students. The determinants of studying history included under this research are the importance of history, and Islamic history. The researchers sampled 315 students as respondents were determined using the snowball technique who answered the online survey developed through Google forms with an appended consent form. The survey link was sent to the student respondents via social media. These students studying at Jeddah University, King Abdelaziz University, and King Saud University. Their ages ranged from 17 to more than 39 years. The results of this study reveal a strong, positive and significant correlation between studying history and student awareness, student awareness and the importance of history as well as student awareness and Islamic history.